2014
DOI: 10.1080/21501203.2014.929600
|View full text |Cite
|
Sign up to set email alerts
|

Sporothriolide derivatives as chemotaxonomic markers forHypoxylon monticulosum

Abstract: During the course of a screening for novel anti-infective agents from cultures of tropical Xylariaceae originating from French Guiana and Thailand, pronounced antifungal activity was noted in extracts of cultures of Hypoxylon monticulosum. A bioassay-guided fractionation led to the known metabolite sporothriolide as active principle. In addition, three new derivatives of sporothriolide were isolated, for which we propose the trivial names sporothric acid, isosporothric acid and dihydroisosporothric acid. Their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 36 publications
2
33
1
Order By: Relevance
“…Fermentation was aborted after free glucose has been consumed and the mycelia was separated from the culture broth by vacuum filtration. The extraction of both parts followed a previously published protocol (Surup et al 2014). The crude extracts were dissolved in acetone and analyzed with HPLC-MS according to Kuhnert et al (2014b).…”
Section: Hplc Profiling Of Culture Extractsmentioning
confidence: 99%
“…Fermentation was aborted after free glucose has been consumed and the mycelia was separated from the culture broth by vacuum filtration. The extraction of both parts followed a previously published protocol (Surup et al 2014). The crude extracts were dissolved in acetone and analyzed with HPLC-MS according to Kuhnert et al (2014b).…”
Section: Hplc Profiling Of Culture Extractsmentioning
confidence: 99%
“…As various other transformants did not show increased production of oryzines it can be speculated that the regulation of gene expression within the oryzine BGC was influenced by the random insertion of the heterologous expressed tenS gene into the A. oryzae genome. Related compounds such as piliformic acid 10 are known to be derived from fatty acids and oxaloacetate [ 28 ]; while the furofuranones 4- epi -ethiosiloide 14 , sporothriolide 15 and discosiolide 16 , are also thought to be derived from fatty acids and oxaloacetate [ 29 , 30 ]. These compounds differ from 3 and 10 by having differing carbon-chain lengths, and by a different lactonisation pattern.…”
Section: Discussionmentioning
confidence: 99%
“…However, the secondary metabolism of these fungi is so diverse that most compounds produced during their life cycle have not yet been identified. Many metabolites that exhibit prominent biological activities are indeed only produced by the cultures (Surup et al 2014) or in the growing stromata bearing the anamorph , and several were only identified after large-scale biotechnological production and extensive chromatographic work (Kuhnert et al 2015;Surup et al 2018).…”
Section: Introductionmentioning
confidence: 99%